2017
DOI: 10.1117/12.2254584
|View full text |Cite
|
Sign up to set email alerts
|

Association between hemodynamic modifications and clinical outcome of intracranial aneurysms treated using flow diverters

Abstract: Treatment of intracranial aneurysms (IAs) has been revolutionized by the advent of endovascular Flow Diverters (FDs), which disrupt blood flow within the aneurysm to induce pro-thrombotic conditions, and serves as a scaffold for endothelial ingrowth and arterial remodeling. Despite good clinical success of FDs, complications like incomplete occlusion and post-treatment rupture leading to subarachnoid hemorrhage have been reported. In silico computational fluid dynamic analysis of the pre- and post-treated geom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 14 publications
1
24
0
Order By: Relevance
“…CFD analysis has also been performed to evaluate the effectiveness of devices such as flow diverter (FD) stents or embolic coils, by observing the blood flow changes between pre-and post-device application in treated aneurysms. 8,10,26,33,34 Paliwal et al 26 analyzed the blood flow of FD stented aneurysms for 15 cases, including 10 complete occlusions and 5 partial occlusions. The results showed that a higher reduction rate in vortex core line length and energy loss occurred for the complete occlusion cases.…”
Section: Simulation Of Endovascular Devicesmentioning
confidence: 99%
“…CFD analysis has also been performed to evaluate the effectiveness of devices such as flow diverter (FD) stents or embolic coils, by observing the blood flow changes between pre-and post-device application in treated aneurysms. 8,10,26,33,34 Paliwal et al 26 analyzed the blood flow of FD stented aneurysms for 15 cases, including 10 complete occlusions and 5 partial occlusions. The results showed that a higher reduction rate in vortex core line length and energy loss occurred for the complete occlusion cases.…”
Section: Simulation Of Endovascular Devicesmentioning
confidence: 99%
“…32 The flow inside the aneurysm is then driven by the pressure instead of by the hemodynamics (Fig 1). 36 Berg et al evaluated flow reductions using CFD and virtual stent placement in aneurysms treated with PED. 34 Chong et al conducted computational flow dynamic (CFD) simulation on 8 patients with intracranial aneurysms who had been treated with a SILK (Balt, Montmorency, France) FD, 4 successfully and 4 unsuccessfully.…”
Section: Mechanism: Overviewmentioning
confidence: 99%
“…Importantly, the degree to which the complex hemodynamic parameters are reduced is related to subsequent successful occlusion, with residual filling on follow-up computed tomographic angiography demonstrated among those patients with a less significant reduction in complex flow parameters. 36 Berg et al evaluated flow reductions using CFD and virtual stent placement in aneurysms treated with PED. There was always a flow reduction after flow diversion (FDS) independent of the treatment success at 1 year.…”
Section: Mechanism: Overviewmentioning
confidence: 99%
“…However, the small PVRR differences among the 3 groups put in perspective the role of flow reduction as a driving parameter in the long-term occlusion of aneurysms treated by FDS. Other parameters should be also considered for a comprehensive understanding of IA thrombosis as suggested by the following studies: Paliwal et al 18 showed that the average velocity reduction was not different between successful (52.4%) and unsuccessful (49.2%) treatments in 15 patients. Similarly, Berg et al 27 studied 2 morphologically equivalent carotid-ophthalmic aneurysms presenting with completely different outcomes (3-month occlusion for one and 3 additional layers required for the other) and found opposite hemodynamic changes.…”
Section: Flow Reduction and Thrombosis Outcomesmentioning
confidence: 99%
“…At present, the quantitative assessment of aneurysmal flow changes relies on 3 main methods: 1) video densitometry based on DSA time-series, 14,15 2) blood flow modeling using computational fluid dynamics (CFD), [16][17][18] and 3) 2D and 4D phase-contrast MR imaging (4D-PCMR). The latter presents the major advantage of being the only quantitative method for the in vivo measurement of 3D velocity fields over time, and some neurovascular disorders have been addressed with this technique, such as arteriovenous malformation hemodynamics.…”
mentioning
confidence: 99%